Free diet selection by broilers as influenced by dietary macronutrient ratio and corticosterone supplementation. 1. Diet selection, organ weights, and plasma metabolites - Malheiros, R. D.; Moraes, V. M B [UNESP]; Collin, A.; Decuypere, E.; Buyse, J. (Elsevier, 2003)
Male broiler chickens (aged 21 d) were allowed to chose freely for 14 d between three diets in which only one specific macronutrient (protein, lipid, or carbohydrate) was isocalorically substituted for one other macronutrient, but otherwise (nearly) isocaloric and composed of the same ingredients. The three diets were low protein (LowCP; 15.81% CP; 6.56% lipid; 50.78% carbohydrate), low lipid (LowL; 19.63% CP; 3.01% lipid; 51.12% carbohydrate), and low carbohydrate (LowCHO; 19.50% CP; 7.72% lipid; 44.00% carbohydrate). The chickens either received 0, 30, or 45 mg of corticosterone (CORT) per kg diet. As a percentage of their total intake, unsupplemented chickens consumed 24.0, 71.4, and 4.6% of the LowCP, LowL, and LowCHO diets, respectively, giving a total CP, L, and CHO intake of 282, 61, and 765 g, respectively. The addition of CORT significantly changed the diet selection, as compared to the unsupplemented chickens, CORT chickens consumed a greater percentage from the LowCP (35%), less from the LowL (55%), and again more from the LowCHO (10%) diet. On the other hand, total feed consumption, macronutrient, and ME intake were not altered significantly by CORT supplementation, probably because of the close similarity of the diets. Corticosterone-supplemented chickens manifested hyperglycemia, hyperlipidemia, and uric acidemia suggesting insulin resistance, increased lipogenesis and protein catabolism, respectively. The elevated plasma creatine kinase (CK) activities of CORT chickens are also suggestive for decreased muscle cell membrane stability. Furthermore, CORT chickens were characterized by increased proportional weights of liver, abdominal fat pad, proventriculus, and gizzard, whereas an involution of spleen and bursa was observed. In conclusion, the present results suggest that high circulating levels of CORT as in the case of stress results in metabolic alterations, which in turn, affects diet preference as a compensatory mechanism to adapt energy and nutrient metabolism.
Keywords: Corticosterone; Diet selection; Macronutrient; Stress; Aves; Gallus gallus; corticosterone; creatine kinase; fatty acid; lipid; triacylglycerol; uric acid; adipose tissue; animal; avian stomach; blood; body weight; caloric intake; carbohydrate diet; chicken; diet; drug effect; fat intake; food preference; glucose blood level; histology; liver; male; metabolism; organ size; physiology; protein intake; Adipose Tissue; Animals; Blood Glucose; Body Weight; Chickens; Creatine Kinase; Diet; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; Fatty Acids, Nonesterified; Food Preferences; Gizzard; Lipids; Liver; Male; Organ Size; Triglycerides; Uric Acid